Motor tics evoked by striatal disinhibition in the rat - Bronfeld, Maya; Yael, Dorin; Belelovsky, Katya; Bar‐Gad, Izhar (Frontiers in Systems Neuroscience, 2013)
Motor tics are sudden, brief, repetitive movements that constitute the main symptom of Tourette syndrome (TS). Multiple lines of evidence suggest the involvement of the cortico-basal ganglia system, and in particular the basal ganglia input structure – the striatum in tic formation. The striatum receives somatotopically organized cortical projections and contains an internal GABAergic network of interneurons and projection neurons collaterals. Disruption of local striatal GABAergic connectivity has been associated with TS and was found to induce abnormal movements in model animals. We have previously described the behavioral and neurophysiological characteristics of motor tics induced in monkeys by local striatal microinjections of the GABAA antagonist bicuculline. In the current study we explored the abnormal movements induced by a similar manipulation in freely moving rats. We targeted microinjections to different parts of the dorsal striatum, and examined the effects of this manipulation on the induced tic properties, such as latency, duration and somatic localization. Tics induced by striatal disinhibition in monkeys and rats shared multiple properties: tics began within several minutes after microinjection, were expressed solely in the contralateral side, and waxed and waned around a mean inter-tic interval of 1-4 s. A clear somatotopic organization was observed only in rats, where injections to the anterior or posterior striatum led to tics in the forelimb or hindlimb areas, respectively. These results suggest that striatal disinhibition in the rat may be used to model motor tics such as observed in TS. Establishing this reliable and accessible animal model could facilitate the study of the neural mechanisms underlying motor tics, and the testing of potential therapies for tic disorders.